Financial transfers from adult children and depressive symptoms among mid-aged and elderly residents in China - evidence from the China health and retirement longitudinal study - Yue Wu; Wanyue Dong; Yongjian Xu; Xiaojing Fan; Min Su; Jianmin Gao; Zhongliang Zhou; Louis Niessen; Yiyang Wang; Xiao Wang (BMC, 2018)
Abstract Background Although the awareness of mental health problems in late life is rising, the association between financial transfers to the older generations from children and mental health at older ages in China has received little attention. This study examines the association between financial transfers from children and depressive symptoms among the mid-aged and elderly residents (from 45 years of age and older) in China. Methods We used the data from the China Health and Retirement Longitudinal Study (CHARLS, 2013) (n = 10,935) This included data on financial transfers from all non-co-resident children to their parents, and the individual scores on depressive symptoms as measured by the 10-item Center for Epidemiologic Studies-Depression Scale (CESD-10). A two-level - individual and community levels - mixed linear model was deployed to explore their association. Results Financial transfers from children to parents was the major component of inter-generational financial transfers in Chinese families. A higher financial support from non-co-resident children was signivicantly and positively related to fewer depressive symptoms (coef. = − 0.195,P-value< 0.001) among both the mid-aged and elderly parents. Conclusions Financial transfers from non-co-resident children are associated with depressive symptoms among mid-aged and elderly residents in the China situation. Taxation and other policy measures should encourage and facilitate these type of financial transfers and prevent a decrease of support from children to parents.